Temperature-mediated switching of protectant-denaturant behavior of trimethylamine-N-oxide and consequences on protein stability from a replica exchange molecular dynamics simulation study. Issue 1 (2nd January 2017) - Borgohain, Gargi; Paul, Sandip
Abstract: The detailed mechanism of protein folding–unfolding processes with the aid of osmolytes has been a leading topic of discussion over many decades. We have used replica-exchange molecular dynamics simulation to propose the molecular mechanism of interaction of a 20-residue mini-protein with urea and trimethylamine N-oxide (TMAO) that act as denaturing and protecting osmolyte, respectively, in binary osmolyte solutions. Urea is found to exert its action by interacting directly with the protein residues. Temperature tolerance of TMAO's action is particularly emphasised in this study. At lower range of temperature, TMAO acts as a successful protein protectant. Interestingly, the study discloses the tendency of TMAO molecules to prefer self-association at the protein surface at elevated temperature. A greater number of TMAO molecules in the protein hydration shell at higher temperature is also observed. Dihedral angle principal component analysis and free energy landscape plots sampled all possible conformations adopted by the protein that reveal highly folded behaviour of the protein in pure water and binary TMAO solutions and highly unfolded behaviour in presence of urea.